The role of the knowledge elite in the development of cross-border cooperation and the culture of peace in the Balkans - Mitrović, Dragana; Velickovic, Dunja; Mitrovuć, Ljubiša (Serbian political thought, 2023)
The contemporary Balkans is still an area of ​​unfinished peace. Its pacification and development depend on a faster process of regionalization and globalization, but also on changing the transition strategy and opening up to the elites of knowledge as actors in the economic, social and cultural development of the countries of this region. Current flows in the European integration processes are predominantly dictated by geostrategic interests, but not by development goals.               The paper discusses the actors of cross-border cooperation in the Balkans, with special reference to the role of the knowledge elite and the new diaspora in regional development and the affirmation of the culture of peace in this fragile geopolitical space. The focus is on the problematization of the thesis on the role of the new intellectual diaspora from the Balkans, which is an integral part of the global transnational actors of social changes in modern times and whose cognitive, innovative and social capital - through the process of return mobility (circular migrations of knowledge elites) can contribute to faster local, national and regional development.               The attachment indicates the high creative-innovative potential of the new Balkan diaspora, embodied in the elites of knowledge, innovators, managers, entrepreneurs in the world, which can be included in the partnership program for local, national and regional development with the new wise policy of nomenclature in the region. This requires the redefinition of the ruling strategy of dependent modernization and comprador development management and the establishment of a new autonomous policy of social development based on local wisdom ("ours and the world's") on intensive intra-regional connection/integration and reactualization of the value of the slogan "Balkans - Balkan peoples!"               Sociological research conducted in the last twenty years shows the slowness of cross-border cooperation processes in the region, the still high degree of exchange with countries outside the region, and the identity perception of the student population is focused on national or European values, while regional values ​​are neglected. It is time to change these priorities in identification, which will be connected with real processes of cross-border cooperation and strengthening of understanding and culture of peace in the Balkans.
Keywords: Development in Balkan; cross-border cooperation; elites of knowledge; cultur of peace